Jak się opowiada o „obrazie nie-do-powiedzenia” — przypadek ekfrastycznego apokryfu (Kobieta w oknie Joyce Carol Oates) - Julia Dynkowska (Zagadnienia Rodzajów Literackich)
This paper is a close-reading of Joyce Carol Oates’ short story The Woman in the Window inspired by Edward Hopper’s 11 A.M. An extensive narrative, which is overwritten over the painting and set in it’s space-time framework, enables the short story discussed herein to be considered as an ekphrastic apocryphon with subversive potential. Literary reaffirmation of the perspective of painted woman that is obviously omitted in Hopper’s masterpiece, allows for the alleged oppressiveness of the painting to be revealed.